The Effect of Mass Fraction of Rice Straw Fiber on The Mechanical Properties and Water Absorption of Cassava Starch Biocomposite - Robertoes Koekoeh Koentjoro Wibowo; Sumarji; Hauzan Nafis Robbani (International Journal of Integrated Engineering, 2025)
The massive use of plastic packaging has a detrimental impact on theenvironment. Alternative solutions are needed, such as replacing plasticwith biocomposites. In this study, biocomposites were made from ricestraw fiber and cassava starch using the solution casting method. Themass fraction of rice straw fiber was varied at 74%, 78%, 82%, 86%, and90%. To determine the characteristics of the biocomposites, tensiletesting, bending testing, water absorption testing, macro observation, andScanning Electron Microscope (SEM) observation were conducted. Theresults showed that as the mass fraction of rice straw fiber increased, themechanical properties of the biocomposites decreased and waterabsorption increased. The ultimate tensile strength, tensile modulus, andelongation at break in the tensile test decreased by 79.95%, 66.65%, and40.45%, respectively. The bending test results showed a decrease inflexural strength and flexural modulus by 78.53% and 70.37%,respectively. The water absorption test results showed an increase inwater absorption by 49.1%. Macro and SEM fracture morphologyobservations revealed the presence of voids, agglomeration, and fiberspulled out of the matrix due to weak interfacial bonding, which caused thelow mechanical properties and high water absorption. This study alsocompared rice straw fiber/cassava starch biocomposites with commercialegg tray samples. The results indicated that rice straw fiber/cassavastarch biocomposites have superior mechanical properties and lowerwater absorption, suggesting their potential use as biocompositepackaging products.